Detrimental effect of apoptosis of lymphocytes at an early time point of experimental abdominal sepsis - Atmatzidis Stefanos; Koutelidakis Ioannis M; Chatzimavroudis Grigorios; Kotsaki Antigone; Louis Konstantinos; Pistiki Aikaterini; Savva Athina; Antonopoulou Anastasia; Atmatzidis Konstantinos; Giamarellos-Bourboulis Evangelos J (BMC Infectious Diseases, 2011)
Abstract Background Apoptosis of lymphocytes is considered a late sequelum in the sepsis cascade. The role of apoptosis of lymphocytes as a driver of final outcome was investigated. Methods Abdominal sepsis was induced after cecal ligation and puncture (CLP) in 31 rabbits. Blood was sampled at serial time intervals and peripheral blood mononuclear cells (PBMCs) were isolated. Apoptosis of lymphocytes and monocytes was measured through flow cytometric analysis. PBMCs were stimulated with LPS and Pam3Cys for the release of tumor necrosis factor-alpha (TNFα). Tissue bacterial growth was quantitatively measured. In a second set of experiments, CLP was performed in another 40 rabbits; 20 received single intravenous infusions of ciprofloxacin and of metronidazole 4 hours after surgery. Results Animals were divided into two groups based on the percentage of lymphocyte apoptosis at 4 hours after surgery; less than or equal to 32% and more than 32%. Survival of the former was shorter than the latter (p: 0.017). Tissue growth was similar between groups. Apoptosis of lymphocytes and of monocytes was lower in the former group over follow-up. Release of ΤNFα did not differ. The above findings on survival were repeated in the second set of experiments. Administration of antimicrobials prolonged survival of the former group (p: 0.039) but not of the latter group (pNS). Conclusions Lymphocyte apoptosis at an early time point of experimental peritonitis is a major driver for death. A lower percentage of apoptosis leads earlier to death. Antimicrobials were beneficial even at that disease state.